IgG4 related lung disease extending to the thoracic vertebrae. (2016) - Stamatopoulos, Alexandros; Patrini, Davide; Koletsis, Efstratios; Borg, Elaine; Khiroya, Reena; Hayward, Martin; Lawrence, David; Panagiotopoulos, Nikolaos
Abstract: IgG4-related disease (IgG4-RD) is a fibroinflammatory condition that can affect practically every organ. Although it was first identified in pancreas and salivary glands, major organs like liver, biliary tree, kidney, thyroid glands and lungs are commonly involved, sometimes resulting in organ failure. We describe a case of an 41-year-old man presented with back pain after a rotator cuff injury. A Computed Tomography (CT) revealed incidentally a right lower lobe paravertebral lesion extending across the T5 and T6 vertebral levels and invading into the adjacent pleural surface. The laboratory findings and the CT guided biopsy were inconclusive. Morphological and immunohistochemical findings after a lung biopsy by video-assisted thoracic surgery (VATS) were suggestive to IgG4-related lung disease (IgG4-RLD), which was confirmed with high serum levels of IgG4. This represents the first case of a IgG4-RLD lesion located in the mediastinum and extending to the adjacent pleural surface and vertebrae and should be included in the differential diagnosis of posterior mediastinal masses.